Synthetic Unity as Gestalt: Gurwitsch’s reading of Gestalt Theory via Kant and Phenomenology (Phenomenology, Humanities and Sciences, 2022)
The main goal of this essay is to suggest that both Gurwitsch’s reinterpretation of phenomenology in Gestalt theory terms and his critical approach to Husserl are based on a fun-damental rereading of two Kant doctrines developed in his Critique of Pure Reason: the doc-trine of the synthetic unity of manifold and the doctrine of the synthetic unity of apperception. We propose that this indicates that the core concepts of Gestalt Psychology have been transcen-dentally structured. Ultimately, it allows for a critical approximation of Gestalt Psychology and transcendental phenomenology. In this regard, we will first revisit Kant’s Transcendental Deduc-tion and develop its nuclear moments as they pertain to the issue of synthesis. Second, we will demonstrate how Gurwitsch employs Gestalt Psychology in an epistemological sense, placing and presenting its premises in a remarkable framework, far from the original aims of its precur-sors. Finally, we will present how his reinterpretation of Gestalt Psychology implies the structure of Kant’s Transcendental Deduction and how it may be used to criticize idealistic assumptions found in diverse philosophical traditions, also including Kant and certain Husserl claims.
Keywords: Phenomenology; Philosophy; Perception; Phenomenological Psychology